THE EFFECT OF COMBINATION OF MARMET TECHNIQUES AND WARM COMPRESSES ON PRODUCTION ASI IN POSTPARTUM MOTHER IN INDEPENDENT MIDWIFE PRACTICE DINCE SAFRINA PEKANBARU CITY - Merlin, Lela; ., Lailiyana; Harahap, Juraida Roito (JURNAL IBU DAN ANAK, 2020)
Abstract Breastfeeding problems that can arise from the first day to the third daypostpartum is ASI not streamlined. ASI does not streamlined make themother unable to meet the needs of the baby. The purpose of this studywas to determine the effect of a combination of the technique marmet andwarm compresses on milk production. The study was conducted in August2019 until April 2020 in PMB Dince Safrina City of Pekanbaru. This typeof research is quantitative research using a Quasi Experiment design. Thepopulation in this study were all postpartum mothers in January-February2020 who delivered at PMB Dince Safrina totaling 27 people. Thesample in this study were 20 postpartum mothers taken with incidentalsampling technique. Data collection uses the observation method using anobservation sheet. Data analysis used independent t test with asignificance level of 95%. The results showed that the average milkproduction in the combination intervention group was 107.00 ml (SD22.63) compared to the marmet technical intervention group which was77.00 ml (SD 27.10). The conclusion of the study is the influence of thetechnique of marmet with and without warm compresses on milkproduction in postpartum mothers (p = 0, 015), it intended thecombination of marmet technique and warm compresses is more effectivein increasing milk production. The advice given is that a combination of themarmet technique and warm compresses can be applied in midwiferycare for postpartum mothers to help increase and expedite milkproduction.